Pengembangan Modul Membaca Kritis dengan Pendekatan Reflektif di SMP Kelas VIII - Usman Usman; Siti Nurhaliza (Nuances of Indonesian Language, 2021)
Research purpose to: (1) determine the level of need for the critical reading module of exposition text with reflective learning in grade VIII of junior high school; (2) produce a critical reading module for exposition text with reflective learning in grade VIII of junior high school that students can use to learn; (3) test the feasibility of the critical reading module of exposition text with reflective learning in grade VIII of junior high school. This research is a research and development designed with R2D2 (Recursive, Reflective Design and Development Model). The data in this study are qualitative and quantitative data from expert and practitioner tests. Qualitative data are sourced from comments, criticisms, and suggestions from expert and practitioner ratings of the module. Quantitative data is sourced from expert and practitioner assessments of module components. The data analysis technique of this research is qualitative data analysis and quantitative data analysis. This research and development resulted in the product of the Critical Text Exposition Reading Module with a ReflectiveApproach in Grade VIII of Junior High School which was assessed by experts and practitioners. The results of expert and practitioner assessments of the module indicate that the assessment in the category is very feasible. The critical reading module of exposition text with a reflective approach was declared very feasible to improve critical reading skills as well as providing knowledge about exposition text to students of grade VIII junior high school.